Pengaruh harga diskon, kualitas produk, citra merek, dan iklan terhadap minat beli celana jeans Levi’s di Surabaya - Ignatius Danu Ghristian (Journal of Business & Banking, 2015)
The aim of this study is to test the effect of Discounted Price, Product Quality, Brand Image, and Advertising on Purchase Intention of Levi’s Pants Jeans in Surabaya. This study used the independent variables such as discount price, product quality, brand image and advertising while the dependent variable is Purchase Intention. It took 82 respondents that were selected by using Judgment Sampling Technique. The data were analyzed using multiple linear regressions and using analysis tools of SPSS version 16.00. The results showed that Discounted Price, Product Quality, Brand Image and Advertising have positive and significant effect on Purchase Intention. The implication was that jeans product with good quality and good image, while need to be advertised need to be leveraged with pricing strategy leading to reducing price.